Lightweight composite from fly ash geopolymer and glass foam. Issue 1 (2nd January 2021) - Kristály, Ferenc; Szabó, Roland; Mádai, Ferenc; Debreczeni, Ákos; Mucsi, Gábor
Abstract : This article is focused on the development of geopolymer–glass foam composite, produced by encapsulation of glass waste based lightweight aggregate in geopolymer matrix. The aim of the investigation was to encase glass foam with optimum cell size in geopolymer in order to obtain lightweight environmentally friendly concrete from waste materials. Physical properties (uniaxial strength and specimen density) of the geopolymer–glass foam composite were determined, while XRD, SEM and FTIR measurement were carried out to investigate the structure of the resulted composite. The density of the composite compared with the neat geopolymer decreased by 76%. XRD results show that amorphous gel was developed from fly-ash and glass foam. The SEM results confirmed the zeolite crystallization and revealed the gel reinforcing arrangement of it. FTIR results show difference in the material structure between the inner part of geopolymer matrix and the interface of geopolymer–glass foam.